2021
DOI: 10.1029/2021ja029508
|View full text |Cite
|
Sign up to set email alerts
|

Radially Full Reflection of Fast Magnetosonic Waves Near the Cut‐Off Frequency

Abstract: Fast magnetosonic (MS) waves have been found to propagate mainly in the radial direction inside the plasmasphere. One main topic about the radial propagation of MS waves is whether they would propagate down to the ground or be reflected at some regions. Since WKB assumption might become invalid near the reflection point (if the reflection happens), an analytic approach has been utilized to investigate the propagation behavior of MS waves in this study. It is found that as MS waves propagate inward into the Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The total reflection at qj(x)=0 ${q}_{j}(x)=0$ in the x direction can be described by the Airy equation and its analytical solutions, as has been demonstrated by Yu et al. (2021). Other couplings can also occur between ±q1 $\pm {q}_{1}$ and ±q2 $\pm {q}_{2}$, even when not connected.…”
Section: Theoretical Modelingmentioning
confidence: 78%
“…The total reflection at qj(x)=0 ${q}_{j}(x)=0$ in the x direction can be described by the Airy equation and its analytical solutions, as has been demonstrated by Yu et al. (2021). Other couplings can also occur between ±q1 $\pm {q}_{1}$ and ±q2 $\pm {q}_{2}$, even when not connected.…”
Section: Theoretical Modelingmentioning
confidence: 78%
“…MS waves can propagate both radially and azimuthally (e.g., Chen & Thorne, 2012;Hanzelka et al, 2022;Kasahara et al, 1994;Němec et al, 2013;Santolík et al, 2016;, and across the plasmapause into the plasmasphere when excited outside of the plasmasphere (e.g., Liu et al, 2018;Min et al, 2019;Xiao, Zhou, et al, 2015). MS waves can further propagate to extremely low L shells ( 𝐴𝐴 𝐴𝐴 𝐴 2.0 ) (e.g., Miyoshi et al, 2019;Yu et al, 2021;Zhang et al, 2021) with some even reaching the topside ionosphere observed by DEMETER (Detection of Electromagnetic Emissions Transmitted from Earthquake Regions) (e.g.,…”
Section: Introductionmentioning
confidence: 99%
“…MS waves can propagate both radially and azimuthally (e.g., Chen & Thorne, 2012; Hanzelka et al., 2022; Kasahara et al., 1994; Němec et al., 2013; Santolík et al., 2016; Xiao, Zhou, et al., 2012), and across the plasmapause into the plasmasphere when excited outside of the plasmasphere (e.g., Liu et al., 2018; Min et al., 2019; Xiao, Zhou, et al., 2015). MS waves can further propagate to extremely low L shells (L<2.0 $L< 2.0$) (e.g., Miyoshi et al., 2019; Yu et al., 2021; Zhang et al., 2021) with some even reaching the topside ionosphere observed by DEMETER (Detection of Electromagnetic Emissions Transmitted from Earthquake Regions) (e.g., Hanzelka et al., 2022; Němec et al., 2016; Santolík et al., 2016). Geomagnetic field strength increases as MS waves propagate toward the Earth and the effects of heavy ions on the propagation start becoming important when the wave frequency becomes lower than the local proton cyclotron frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS waves usually propagate as whistler mode with very large normal angles (e.g., Boardsen et al., 2016; Russell et al., 1970; Stix, 1992) and both radial and azimuthal propagation (e.g., Chen & Thorne, 2012; Hanzelka et al., 2022; Liu et al., 2018; Min et al., 2019; Santolík et al., 2016; Xiao et al., 2012b, 2015b) may be affected by the gradient of electron density. The effects of ions become of significance when MS waves propagate to the location where the frequency is around or below the local proton cyclotron frequency (e.g., Miyoshi et al., 2019; Santolík et al., 2016; Yu et al., 2021). EMIC waves usually propagate along the magnetic field line to higher latitudes after excitation near the equatorial region (e.g., Loto'aniu et al., 2005; Zhang et al., 2014; Q. H. Zhou et al., 2013).…”
Section: Introductionmentioning
confidence: 99%